Between Patton and Montgomery: Robert Henriques and Operation Husky. (April 2021) - Barr, Niall
This article explores the role and importance of General Patton's unofficial British liaison officer, Col. Robert Henriques, during Operation Husky, July–August 1943. In so doing, it sheds further light upon some of the most famous disputes between the Allies and highlights the importance of liaison and the consequences of its relative dearth to Anglo–American relations during the campaign. Henriques experience and involvement also reveal a small part of the Allies use of special forces during the campaign. Overall, Henriques role and experience provide a valuable and detailed perspective on Operation Husky.